2013
DOI: 10.1074/jbc.m113.450635
|View full text |Cite
|
Sign up to set email alerts
|

Signal Relay by CC Chemokine Receptor 2 (CCR2) and Formylpeptide Receptor 2 (Fpr2) in the Recruitment of Monocyte-derived Dendritic Cells in Allergic Airway Inflammation

Abstract: Background: Chemoattractant receptor Fpr2 interacts with host-derived agonists and mediates leukocyte trafficking. Results: In the lung of allergic inflammation, chemokine receptor CCR2 elicits accumulation of monocyte-derived DC in perivascular region, but Fpr2 is critical for cell trafficking to peribronchiolar area. Conclusion: CCR2 and Fpr2 sequentially guide DC trafficking in inflamed lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 51 publications
2
42
0
Order By: Relevance
“…CCR2 is a chemokine receptor expressed on the cell surface of inflammatory monocytes and moDCs and is involved with facilitating their migration to sites of inflammation (24,25). Indeed, the absence of CCR2 has been found to result in a significant reduction in the recruitment of moDCs in response to infection (26,27) or allergic disease (28). Consistent with previous reports of moDCs arising in other inflammatory contexts, we confirmed that the allogeneic Ag-induced splenic moDCs we observed were CCR2 + (Fig.…”
supporting
confidence: 81%
“…CCR2 is a chemokine receptor expressed on the cell surface of inflammatory monocytes and moDCs and is involved with facilitating their migration to sites of inflammation (24,25). Indeed, the absence of CCR2 has been found to result in a significant reduction in the recruitment of moDCs in response to infection (26,27) or allergic disease (28). Consistent with previous reports of moDCs arising in other inflammatory contexts, we confirmed that the allogeneic Ag-induced splenic moDCs we observed were CCR2 + (Fig.…”
supporting
confidence: 81%
“…Whereas activation of FPRL1 by serum amyloid A induced CCL2 production in human endothelial cells, CCL2 acts synergistically with FPR ligand fMLF. 44,45 Chen et al 46 demonstrated that interaction of the chemokine receptor CCR2, the receptor for CCL2, and FPR2 with their endogenous ligands sequentially mediated the trafficking of dendritic cells within the inflamed lung. Our in vitro results with glial cell stimulation showed that the lack of FPR1 resulted in a comparable to stronger induction of chemokine expression compared with WT glia cells, whereas FPR2 deficiency led to attenuated over-expression.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation revealed that there is a significantly reduced recruitment of Ly6C ϩ inflammatory DCs into the bronchiolar area in the allergic inflammatory airway of Fpr2 Ϫ/Ϫ or CRAMP Ϫ/Ϫ mice, suggesting that Fpr2 and its endogenous ligand CRAMP control DC trafficking (1).…”
mentioning
confidence: 99%
“…Leukocyte trafficking and homing are mediated by G protein-coupled receptors (GPCRs) 3 that recognize pathogen and host-derived chemoattractants (1,2). Some chemoattractant GPCRs are involved in both innate and adaptive immune responses (3) and are essential for development, angiogenesis, and homing of antigen presenting dendritic cells (DCs) (4).…”
mentioning
confidence: 99%